2021
DOI: 10.3390/ma14205933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical and Permeability Characteristics of Microfiber-Reinforced Recycled Aggregate Concrete with Different Potential Waste Mineral Admixtures

Abstract: Plain recycled aggregate concrete (RAC) struggles with issues of inferior mechanical strength and durability compared to equivalent natural aggregate concrete (NAC). The durability issues of RAC can be resolved by using mineral admixtures. In addition, the tensile strength deficiency of RAC can be supplemented with fiber reinforcement. In this study, the performance of RAC was evaluated with individual and combined incorporation of microfibers (i.e., glass fibers) and various potential waste mineral admixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…The basalt-fiber-reinforced concrete showed improved performance as compared to pure concrete as well as fine-/coarse-aggregate-based samples. Similar studies have been reported in the literature where the performance of concrete was improved by an addition of up to 3% microfibers and waste mineral admixtures [ 42 ].…”
Section: Resultssupporting
confidence: 86%
“…The basalt-fiber-reinforced concrete showed improved performance as compared to pure concrete as well as fine-/coarse-aggregate-based samples. Similar studies have been reported in the literature where the performance of concrete was improved by an addition of up to 3% microfibers and waste mineral admixtures [ 42 ].…”
Section: Resultssupporting
confidence: 86%
“…Fibres have been reported to be very effective at improving materials properties such as; ductility, impact resistance, toughness and resistance to fatigue [12,13]. With its small weight, high tensile strength, and good toughness, PPF is a superb material for durable concrete [14]. When PPFs are added to concrete, it helps to reduce the pores within the concrete and also improves its resistance to crack [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most efficient method for reducing the negative effects that concrete has on the environment is to reduce the amount of cement that is used in its production. This goal can be accomplished through the use of alternative building materials [ 1 , 2 , 3 ]. Concrete is frequently utilized in industries, which increases its demand and will result in its depletion.…”
Section: Introductionmentioning
confidence: 99%